PENGELOLAAN PENANGKARAN DAN KUALITAS SUARA CUCAK RAWA (Pycnonotus zeylanicus Gmelin, 1789) DI MEGA BIRD AND ORCHID FARM, BOGOR - Dini Ayu Lestari; Burhanuddin Masy'ud; Jarwadi B Hernowo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
The background of this research is population of straw headed bulbul (Pcynonotus zeylanicus) in the nature has decreased sharply.The effort should be done is ex-situ conservation by means of captive breeding of straw headed bulbul. The aim of the research was to identify captivation technique, success indicator, song training techniques and distribution sound quality of straw headed bulbul. This research was conducted in Mega Bird and Orchid Farm, Bogor from March to April 2014. Descriptive and quantitative data analysis was applied in this research. The results showed that straw headed bulbul has three types of cage, they are cage for growing periode, ge of reproduction, and cage of incubator. Foods given to the bird were banana, papaya, voer and cricket. The types of diseases recorded were diarrhea, white-colored feces, green-colored feces, flu, and paralyzed feet. The criteria and success rate in captivating were consist of medium-scaled egg hatching rate (68.69%), high breed rate (77.38%), and low mortality(10.34%). Distribution song quality of straw headed bulbul was varies. Based on the results of the study, it can be concluded that breeding management for success breeding of straw headed bulbul comprised of such aspects as cage system management, feed management, health and care management, result utilization management, and song quality management. Keywords: captive breeding, management, straw headed bulbul